2022
DOI: 10.3389/fimmu.2022.782441
|View full text |Cite
|
Sign up to set email alerts
|

Clonally Expanded Virus-Specific CD8 T Cells Acquire Diverse Transcriptional Phenotypes During Acute, Chronic, and Latent Infections

Abstract: CD8+ T cells play a crucial role in the control and resolution of viral infections and can adopt a wide range of phenotypes and effector functions depending on the inflammatory context and the duration and extent of antigen exposure. Similarly, viral infections can exert diverse selective pressures on populations of clonally related T cells. Technical limitations have nevertheless made it challenging to investigate the relationship between clonal selection and transcriptional phenotypes of virus-specific T cel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
(97 reference statements)
1
10
1
Order By: Relevance
“…On an individual-chain level, similar TCR β V genes were expressed across all infection conditions (Figure S3A, S3B), although on a clonal level, no group-specific pattern of TRAV-TRBV pairings could be observed (Figure S3C). This is in contrast to previously reported results where TCR repertoires against a single peptide demonstrated stereotypic germline gene usage (Kuhn et al 2022), suggesting that polyclonal repertoires encoding diverse TCR specificities are less dominated by certain combinations of germline genes.…”
Section: Cd4+ T Cellscontrasting
confidence: 99%
See 3 more Smart Citations
“…On an individual-chain level, similar TCR β V genes were expressed across all infection conditions (Figure S3A, S3B), although on a clonal level, no group-specific pattern of TRAV-TRBV pairings could be observed (Figure S3C). This is in contrast to previously reported results where TCR repertoires against a single peptide demonstrated stereotypic germline gene usage (Kuhn et al 2022), suggesting that polyclonal repertoires encoding diverse TCR specificities are less dominated by certain combinations of germline genes.…”
Section: Cd4+ T Cellscontrasting
confidence: 99%
“…The abundance of certain TCR V germline genes or their pairings have been previously observed in virus-specific T cells in several infection conditions (Qu et al 2016;Izraelson et al 2018;Welten et al 2020;Yermanos et al 2020;Khatun et al 2021;Kuhn et al 2022). Additionally, a previous study reported preferential usage of TRAV-TRAJ gene combination in Th1 and Tfh cells, indicating a contribution of the TCR α chain to lineage commitment (Khatun et al 2021).…”
Section: Cd4+ T Cellsmentioning
confidence: 79%
See 2 more Smart Citations
“…To demonstrate several use cases of the ePlatypus computational ecosystem, we integrated and analyzed multiple single-cell transcriptomes and immune receptor repertoires across different disease conditions, viral infections, and vaccination studies. We directly downloaded murine T cell repertoires from previously published datasets containing both CD4 and CD8 T cells from conditions such as acute and chronic viral infections (Khatun et al, 2021;Kuhn et al, 2022;Merkenschlager et al, 2021;Shlesinger et al, 2022), homeostatic aging and experimental autoimmune encephalomyelitis (Shlesinger et al, 2022) (Table S2). Following transcriptional integration with Harmony (Korsunsky et al, 2019), which aims to reduce batch effects across different datasets, we visualized all cells using uniform manifold approximation projection (UMAP) (Figure S11A,S11B).…”
mentioning
confidence: 99%